Development of Student Online Consultation System (SOCS) using ADDIE model and UCD approach: a case study at University Kuala Lumpur Malaysian Institute of Information Technology (UniKL MIIT) / Syahrina Shawalludin - Shawalludin, Syahrina (2014)
Online system is of utmost importance today. It is a technology that is useful to be used by the user on their daily life routine. The technologies nowadays are evolving to improve our daily routine work. Almost every work and data processing in office were done manually has change into a computerize system which from using paper to keep data and information has change into saving the data and information in computer. This were call paperless environment where every work and process was stored in a computer system to save the paper cost and to simplify the process of work that take long time to finish. The purpose of Student Online Consultation System (SOCS) was produced in order for students and lecturers of Department of Software Engineering at University Kuala Lumpur Malaysian Institute of Information Technology (UniKL MIIT) to setup appointment and improve communication between students and lecturers and to establish platform where students can submit the file or note to specific lecturers. ADDIE model being used for the development phase in methodology chapter and using User Centered Design (UCD) approach for the design phase in the ADDIE model phase. For the developing process, Adobe Dreamweaver CS4, Coldfusion 9 and Microsoft Sequel (SQL) Server 2008 R2 was chosen to design and build the SOCS prototype. Adobe Dreamweaver CS4 was used for programming platform, Coldfusion 9 being used for connection between the database and the application meanwhile for database platform Microsoft Sequel (SQL) Server 2008 R2 was chosen to be used. The results of this research are the prototype of SOCS. However there are some limitations and recommendation that need to be considered in future research development.